Climate-smart technologies integrating renewable energy and energy efficiency in mitigation and adaptation responses - Leal Filho, Walter (Springer Berlin Heidelberg, 2013)
The book addresses the perceived need for a publication with looks at both, climate smart technologies and the  integration of renewable energy and energy efficiency in mitigation and adaptation responses. Based on a set of papers submitted as part of the fifth on-line climate conference (CLIMATE 2012) and a major conference on renewable energy on island States held in Mauritius in 2012, the book provides a wealth of information on climate change strategies and the role of smart technologies. The book has been produced in the context of the project "Small Developing Island Renewable Energy Knowledge  and Technology Transfer Network" (DIREKT), funded by the ACP Science and Technology Programme, an EU  programme for cooperation between the European Union and the ACP region. Preface -- Part I: Climate change trends and strategies -- Part 2: Renewable energy strategies and methods -- Part 3: Climate smart energy technologies.